2021
DOI: 10.3390/agronomy11061143
|View full text |Cite
|
Sign up to set email alerts
|

Use of Microbial Biostimulants to Increase the Salinity Tolerance of Vegetable Transplants

Abstract: Vegetable plants are more sensitive to salt stress during the early growth stages; hence, the availability of poor-quality brackish water can be a big issue for the nursery vegetable industry. Microbial biostimulants promote growth and vigor and counterbalance salt stress in mature plants. This study aimed to evaluate the application of plant growth-promoting microorganisms for improving salt tolerance of lettuce and tomato seedlings irrigated with different water salinity levels (0, 25, and 50 mM NaCl) during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 110 publications
(146 reference statements)
2
28
0
Order By: Relevance
“…The decrease of plant growth under salt stress may be due to the reduction in cell division and elongation [ 38 ]; there is also a destructive impact of NaCl on different physiological pathways and molecular changes through impaired photosynthesis, nutrient imbalances, stomatal impedance to water flow, alterations in the ultrastructure of chloroplasts and mitochondria (which affect the natural metabolism), and hormonal imbalances [ 39 , 40 ]. Earlier studies [ 25 , 26 , 28 , 41 ] showed that SA could reduce salt damage in various plants. The exogenous application of SA is expected to control stomatal opening under stress, and this decreases transpiration and water loss, sustains turgor, and controls plant growth and productivity under stress conditions [ 33 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decrease of plant growth under salt stress may be due to the reduction in cell division and elongation [ 38 ]; there is also a destructive impact of NaCl on different physiological pathways and molecular changes through impaired photosynthesis, nutrient imbalances, stomatal impedance to water flow, alterations in the ultrastructure of chloroplasts and mitochondria (which affect the natural metabolism), and hormonal imbalances [ 39 , 40 ]. Earlier studies [ 25 , 26 , 28 , 41 ] showed that SA could reduce salt damage in various plants. The exogenous application of SA is expected to control stomatal opening under stress, and this decreases transpiration and water loss, sustains turgor, and controls plant growth and productivity under stress conditions [ 33 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Principal component analyses can be effective in unraveling the effects of several experimental factors (genetic materials, pre-and postharvest management) on yield and quality parameters of many vegetable crops, as reported in many experiments carried out on different species and growing and storage conditions [12,86,96,97,[109][110][111]. This was also the case in the present experiment since the different effects determined by the treatments with E. maxima extract on leaf lettuce plants were clearly shown by the Principal Component Analyses that outlined the various responses of leaf lettuce during growth and storage to the supplementation of different levels of seaweed extract through the nutrient solution.…”
Section: Discussionmentioning
confidence: 99%
“…al., 2016). It has been stated that increasing salt doses reduce yield and quality in plants (Chaudhry et al, 2021;Miceli et al, 2021;Sogoni et al, 2021). As in many parts of the world, the surplus of salty land in our country also creates serious problem in production.…”
Section: Resultsmentioning
confidence: 99%
“…In the study, which determined the salt tolerance of local melons grown in Türkiye, it is stated that the development of new varieties with high tolerance to salty conditions of Koçhisar melon, Van and Mardin melon grown around Tuz Gölü is important for the evaluation (Kuşvuran et al, 2012). In the study of application of microorganisms that promote plant growth to improve the salt tolerance of lettuce and tomato seedlings irrigated with different salinity levels, it is stated that (0, 25 and 50 mM NaCl) salt applications during seedling growth negatively affect many morpho-physiological parameters of lettuce and tomato seedlings (Miceli et al, 2021). In the study results to seven onion cultivars from Türkiye for biochemical and gene expression responses to drought and salt stresses under greenhouse conditions, revealed that the cultivars Perama, İnci, and Seyhan were tolerant, whereas the cultivars Elit and Hazar were grouped as sensitive to salt (Chaudhry et al, 2021).…”
Section: Introductionmentioning
confidence: 99%